2022
DOI: 10.3389/fnins.2022.874750
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Astrocytic Glutamine Transport in Acute Hyperammonemic Brain Edema

Abstract: Acute liver failure (ALF) impairs ammonia clearance from blood, which gives rise to acute hyperammonemia and increased ammonia accumulation in the brain. Since in brain glutamine synthesis is the only route of ammonia detoxification, hyperammonemia is as a rule associated with increased brain glutamine content (glutaminosis) which correlates with and contributes along with ammonia itself to hyperammonemic brain edema-associated with ALF. This review focuses on the effects of hyperammonemia on the two glutamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 211 publications
0
5
0
Order By: Relevance
“…Astrocytes are the exclusive possessors of glutamine synthetase in the brain, 137 which makes them the main target for ammonium. Most of ammonium entering the brain is converted to glutamine, which causes glutaminosis 359 and effectively lowers brain parenchymal ammonium concentrations, but which also maintains the concentration gradient and favours additional entry of ammonium from the blood to the brain. 360 At the cellular level, excess of ammonium mainly affects astrocytes with neuronal injury being secondary, resulting mainly from failure of astrocytic homoeostatic cascades and oedema.…”
Section: Astrocytes As Main Target Of Toxic Encephalopathiesmentioning
confidence: 99%
“…Astrocytes are the exclusive possessors of glutamine synthetase in the brain, 137 which makes them the main target for ammonium. Most of ammonium entering the brain is converted to glutamine, which causes glutaminosis 359 and effectively lowers brain parenchymal ammonium concentrations, but which also maintains the concentration gradient and favours additional entry of ammonium from the blood to the brain. 360 At the cellular level, excess of ammonium mainly affects astrocytes with neuronal injury being secondary, resulting mainly from failure of astrocytic homoeostatic cascades and oedema.…”
Section: Astrocytes As Main Target Of Toxic Encephalopathiesmentioning
confidence: 99%
“…They transport glutamine into synapses while transporting Na + in the same direction and H + in the opposite direction 43,45 . In vitro studies of primary astrocyte cultures have shown that system N contributes between 10% and 50% of the total glutamine transport capacity 46 . Among system N transporters, SLC38A3 is the major transporter for glutamine release in astrocytes, whereas SLC38A5 has a relatively high affinity for serine 46 .…”
Section: Glutamate–glutamine Cyclementioning
confidence: 99%
“… 43 , 45 In vitro studies of primary astrocyte cultures have shown that system N contributes between 10% and 50% of the total glutamine transport capacity. 46 Among system N transporters, SLC38A3 is the major transporter for glutamine release in astrocytes, whereas SLC38A5 has a relatively high affinity for serine. 46 Studies demonstrate that the Km values for glutamine efflux facilitated by SLC38A3 and SLC38A5 are 1.57 and 1.2 mM, respectively.…”
Section: Glutamate–glutamine Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Ammonium circulating in excess enters the brain, where it is detoxified and converted to glutamine by astrocyte resident glutamine synthetase (Brusilow et al, 2010;Cooper et al, 1979). Pathological increase of glutamine in the brain leads to a multifaceted homeostatic imbalance (Zielińska et al, 2022), which is clinically manifested by delirium, hallucinations, acute psychosis, and, in a terminal phase, coma leading to death (Weissenborn, 2019). In HE astrocytes undergo multiple morphological changes (Albrecht & Jones, 1999;Gelpi et al, 2020) ranging from reactive astrogliosis, swelling (that contributes to brain oedema), and the emergence of disease-specific aberrant astrocytes known as Alzheimer type II astrocytes, the term introduced in 1942 (Waggoner & Malamud, 1942).…”
Section: Introductionmentioning
confidence: 99%